Ice and aqueous photochemistry of high-ring chlorinated polycyclic aromatic hydrocarbons: A systematic assessment of persistence and risk in cold regions - Linke Ge; Rongyan Xu; Jack Garnett; Peng Zhang; Dongxiao Bai; Siyuan Wang (Journal of Hazardous Materials, 2026)

New Insights into the Aquatic Photochemistry of Sulfonamide Antibiotics: Apparent Photolysis, Toxicity Evolution and Mechanisms - Linke Ge; Jiahui Wang; Andrew Sweetman; Zhixuan Zheng; Peng Zhang; Nannan Cui (Water, Air, & Soil Pollution, 2026)

Exploring the multiple photochemical behaviors of ionizable EDCs in aquatic environments: Kinetics, intermediates, and toxicity evolution - Linke Ge; Shijing Yang; Nannan Cui; Chang-Er Chen; Xiaojia Che; Peng Zhang (Environmental Research, 2026)

Retention time prediction of emerging contaminants via transfer learning with graph neural networks - Jiewen Deng; Junbin Chen; Jingyi Wang; Xingying Li; Sisi Liu; Linke Ge; Guang-Guo Ying; Chang-Er Chen (Journal of Hazardous Materials, 2026)

Simultaneously sampling sulfonamide antibiotics (SAs) and endocrine disrupting chemicals (EDCs) in aqueous environment by the DGT passive sampler with a novel composite binding gel - Jing Wang; Peng Zhang; Wenjun Chen; Yaqing Cui; Linke Ge; Yinping Hou (Journal of Environmental Chemical Engineering, 2025)

New insights into the environmental photochemistry of hydroxynaphthalene congeners in water and in ice: A distinct comparative study - Linke Ge; Zhimin Hou; Junfeng Niu; Siyuan Wang; Peng Zhang; Yunqing Zhu (Journal of Hazardous Materials, 2025)

Insight into the environmental photochemistry of nitrated polycyclic aromatic hydrocarbons in water and in ice: kinetics, pathways and photo-modified toxicity - Linke Ge; Siyuan Wang; Nannan Cui; Ziyu Wang; Peng Zhang (Environmental Research, 2025)

Dissociation-dependent kinetics and distinct pathways for direct photolysis and •OH/SO4•− radical dominated photodegradation of ionizable antiviral drugs in aquatic systems - Nannan Cui; Linke Ge; Crispin Halsall; Junfeng Niu; Jinshuai Zheng; Peng Zhang (Water Research, 2025)

CO2-activated porous semi-coke for peroxydisulfate activation: Enhanced tetracycline degradation via non-radical pathways - Zhi Hu; Jiahong Wang; Yanxin Zhang; Zekun Xu; Linke Ge (Journal of Water Process Engineering, 2025)

The influence mechanism of environmental factors on DGT adsorbing sulfonamides and the migration between water and sediment - Peng Zhang; Jingfeng Yan; Hao Ji; Linke Ge; Yanying Li (Journal of Environmental Sciences, 2025)

Photochemical properties and toxicity of fluoroquinolone antibiotics impacted by complexation with metal ions in different pH solutions - Shengkai Cao; Peng Zhang; Heming Song; Linke Ge; Junfeng Niu (Journal of Environmental Sciences, 2025)

Aquatic photochemistry for different dissociation forms of cephalosporin antibiotics: Degradation kinetics, products and photo-modified toxicity - Linke Ge; Yadi Guo; Qing Xie; Yan Yang; Peng Zhang; Jiahong Wang; Yunqing Zhu (Environmental Pollution, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Occurrence and seasonal variations of antibiotic micro-pollutants in the Wei River, China - Shengkai Cao; Peng Zhang; Crispin Halsall; Zhimin Hou; Linke Ge (Environmental Research, 2024)

Exploring the aqueous photodegradation of three ionisable macrolide antibiotics: Kinetics, intermediates and photoinduced toxicity - Linke Ge; Nannan Cui; Crispin Halsall; Yan Yang; Shengkai Cao; Peng Zhang (Journal of Water Process Engineering, 2024)

Comparing the photodegradation of typical antibiotics in ice and in water: Degradation kinetics, mechanisms, and effects of dissolved substances - Linke Ge; Xuanyan Li; Shuang Zhang; Shengkai Cao; Jinshuai Zheng; Degao Wang; Peng Zhang (Chemosphere, 2024)

Insight into typical photo-assisted AOPs for the degradation of antibiotic micropollutants: Mechanisms and research gaps - Jinshuai Zheng; Peng Zhang; Xuanyan Li; Linke Ge; Junfeng Niu (Chemosphere, 2023)

Organophosphate esters in the seawater of the Bohai Sea: Environmental occurrence, sources and ecological risks - Rongguang Xing; Peng Zhang; Nan Zheng; Hao Ji; Ren Shi; Linke Ge; Hongrui Ma (Marine Pollution Bulletin, 2023)

Photodegradation of hydroxyfluorenes in ice and water: A comparison of kinetics, effects of water constituents, and phototransformation by-products - Linke Ge; Shengkai Cao; Crispin Halsall; Junfeng Niu; Dongxiao Bai; Guangkai He; Peng Zhang; Hongrui Ma (Journal of Environmental Sciences, 2023)

Exploring the influence of concentration fluctuation and matrix effects on a passive sampler of triolein-embedded cellulose acetate membrane measuring polychlorinated biphenyls in water - Peng Zhang; Linke Ge; Yiping Xu; Ting Yao; Ying Bian; Dongxing Zhou; Xiaozhong Gao (Environmental Science and Pollution Research, 2022)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

Aqueous multivariate phototransformation kinetics of dissociated tetracycline: implications for the photochemical fate in surface waters - Linke Ge; Qianqian Dong; Crispin Halsall; Chang-Er L. Chen; Jun Li; Degao Wang; Peng Zhang; Ziwei Yao (Environmental Science and Pollution Research, 2018)